Implementation of Digital Marketing through Social Media to Increase The Number of Visits at Ujung Suso Beach Tourism, East Luwu District - Syam, Agus; Dajo, Fenly Crosby Cloria; Asmayanti, Asmayanti; Jufri, Muhammad; Halim, Nur (Journal of Applied Business, Taxation and Economics Research, 2024)
This research aims to understand how to improve the number of visitors to the Ujung Suso beach tourist destination after implementing digital marketing. The research method used is qualitative descriptive research. Data collection was carried out through observation, interviews and documentation techniques as well as using Voice of Customer (VOC) analysis. The data collected is processed by data reduction, data presentation, and drawing conclusions. Based on the research results, it shows that the implementation of digital marketing via social media Facebook and Instagram from February to March succeeded in increasing the number of visits to Ujung Suso beach tourism. This is proven by the increase in the number of visitors during the research period compared to the period before the implementation of digital marketing. So it can be said that digital marketing through social media is an effective strategy to increase tourist visits to Ujung Suso beach.